Research on coal mine pressure characteristics based on all-fiber optic micro-seismic monitoring - Wang, Shuo; Wang, Kangdong; Zhao, Zhigen; Miao, Yuanyuan; Cai, Tianyu (Frontiers in Earth Science, 2025)
In the process of coal mining, pressure will be induced in the working face, resulting in the stress concentration of surrounding rock, which will affect the safety and orderly normal operation of coal energy mining. The all-fiber optic micro-seismic monitoring technology offers advantages such as high sensitivity, wide dynamic range, and passive front-end intrinsic safety, resolving the conflict between high sensitivity and broadband frequency response. This technology enhances both the sensitivity and frequency response range of micro-seismic monitoring, enabling effective real-time monitoring of pressure-related activities in coal mines. Taking the II1012 working face of Taoyuan Coal Mine as the engineering background, the all-fiber optic micro-seismic monitoring work is carried out, and the data are analyzed by the methods of micro-seismic event detection, identification, classification and location. The characteristics of micro-seismic activity during the first weighting (the mine pressure appears before and after the primary fracture of the basic roof), periodic weighting (the mine pressure of the old roof is manifested by periodic fracture or collapse) and square pressure (the mining pressure of the working face is equivalent to the length of the cutting hole) are studied. The results show that: High-energy events in the first weighting stage play a major role in roof failure. In the periodic weighting stage, the influence of micro-seismic activity on the roof is greater than that on the floor, but the influence on the floor is increasing. The high-energy events increase significantly in the square pressure stage, which is easy to promote the frequent occurrence of high intensity and stress micro-seismic activities. The occurrence of micro-seismic events in mine pressure phases have advanced characteristics. There is a positive correlation between the intensity of micro-seismic activity and the rate of recovery, and the all-fiber optic micro-seismic has a good response to the mine pressure. The research work provides theoretical basis and technical support guidance for the safe production of the II1012 working face in Taoyuan Coal Mine and other similar working faces in other coal mines, reduces the risk of geological disasters caused by micro-seismic events during the pressure period, and further guarantees the safe and normal orderly development of the subsequent production work of the working face. It is of great significance to the safe mining of coal energy and the supply of production and life.